Prospects for Raman spectroscopy in cardiology - V. V. Rafalsky; A. Yu. Zyubin; E. M. Moiseeva; I. G. Samusev (Кардиоваскулярная терапия и профилактика, 2020)
Raman spectroscopy (RS) is a promising diagnostic method with high informative value and sensitivity. In addition, it is non-destructive and minimally invasive, and also requires minimal sample preparation, which opens up wide prospects for in vitro and in vivo use. There are some perspectives for this method in future cardiology practice. RS may allow to identify previously studied markers of cardiovascular disease, as well as to search for new ones. It is a sensitive method for the detection and biochemical assessment of early-stage atherosclerotic lesions and can be used in vivo. Of great interest is the possibility of using the RS to control the amount of eluted substance from drug-eluting stents to assess clinical efficacy. Study of platelet membranes using the RS technique revealed structural changes in patients with hypertension. This method makes it possible to assess myocardial viability in the border zone after myocardial infarction, and the obtained results correlate with the intraoperative data. More details about the prospects of using the RS will be described in the review.